Powder for dust core, method for producing powder for dust core, dust core and method for producing dust core

A mixed layer of diphenyldimethoxysilane and silicone resin on soft magnetic iron powder enhances heat resistance and insulation in powder magnetic cores, addressing the issue of increased core loss in miniaturized components exposed to high temperatures.

JP7603644B2Active Publication Date: 2024-12-20TAMURA KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022150233
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-21
Publication Date
2024-12-20
Estimated Expiration
2042-09-21

AI Technical Summary

Technical Problem

Miniaturized electrical components require high heat resistance due to reduced heat dissipation areas, and existing insulating layers on soft magnetic iron powder deteriorate with heat, leading to increased eddy current loss and iron loss in powder magnetic cores.

Method used

A mixed layer of soft magnetic iron powder, diphenyldimethoxysilane, and silicone resin is used, with a crosslinked structure, to form a powder magnetic core that maintains insulation and heat resistance even in high-temperature environments.

Benefits of technology

The solution effectively suppresses core loss in powder magnetic cores by improving heat resistance and insulation, maintaining low iron loss even under high-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603644000004
    Figure 0007603644000004
  • Figure 0007603644000005
    Figure 0007603644000005
  • Figure 0007603644000006
    Figure 0007603644000006
Patent Text Reader

Abstract

To provide powders for a powder magnetic core which less generate an iron loss even when the powders are exposed to high temperatures, a method for manufacturing the powders for a powder magnetic core, a powder magnetic core using the powders for a powder magnetic core, and a method for manufacturing the powder magnetic core.SOLUTION: The powders for a power magnetic core include soft magnetic iron powders and a mixture layer covering a part or all of the soft magnetic iron powders. The mixture layer is formed by mixing diphenyldimethoxysilane and silicone resin with each other. The powder magnetic core includes the powders for a powder magnetic core. The powders for a powder magnetic core are manufactured by a mixing step of concurrently mixing diphenyldimethoxysilane and silicone resin in the soft magnetic powders, and a drying step of drying the mixture at a lower temperature than the boiling point of diphenyldimethoxysilane after the mixing step. The powder magnetic core is manufactured by pressure-forming the powders for a powder magnetic core and annealing the formed body after the pressure-forming step.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a powder for dust cores and a dust core containing the powder for dust cores. [Background technology]

[0002] A coil, also called an inductor or reactor, is an electromagnetic component that converts electrical energy into magnetic energy and stores and releases it. Coils, also called reactors in power applications, are used in a variety of fields, including drive systems for hybrid cars, electric cars, and fuel cell cars, as well as office equipment, solar power generation systems, automobiles, and uninterruptible power supplies.

[0003] Coils often use powder magnetic cores. Powder magnetic cores are made by compressing powder for powder magnetic cores into a compact and then annealing it. Powder for powder magnetic cores is soft magnetic metal powder. Examples of soft magnetic metal powder include soft magnetic iron powders such as permalloy (Fe-Ni alloy) which is mainly composed of iron, Si-containing iron alloy (Fe-Si alloy), and sendust alloy (Fe-Si-Al alloy).

[0004] Due to requirements for improved energy exchange efficiency and low heat generation, powder magnetic cores are required to have magnetic properties that allow a large magnetic flux density to be obtained with a small applied magnetic field, and that minimize energy loss when the magnetic flux density changes. The magnetic property related to magnetic flux density is specifically magnetic permeability (μ). The magnetic property related to energy loss is specifically iron loss (Pcv). Iron loss (Pcv) is expressed as the sum of hysteresis loss (Ph) and eddy current loss (Pe).

[0005] Hysteresis loss is proportional to frequency, and eddy current loss is proportional to the square of frequency. Therefore, when using a coil in a high frequency range, eddy current loss dominates energy loss. It is known that eddy current loss increases with increasing magnetic domain width. Therefore, one method of reducing eddy current loss is to insulate the soft magnetic iron powder. By covering the soft magnetic iron powder with an insulating layer, the spaces between the soft magnetic iron powder particles are expanded, the magnetic domains are subdivided, and eddy current loss is reduced.

[0006] The insulating layer that covers the soft magnetic iron powder contains silicone resin. In order to improve the wettability of the soft magnetic iron powder or to increase the bond strength between the silicone resin and the soft magnetic iron powder, a method has been proposed in which a silane coupling agent is mixed with the soft magnetic iron powder and dried to form a base layer for the silicone resin before covering the soft magnetic iron powder with the silicone resin (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2003-303711 A Summary of the Invention [Problem to be solved by the invention]

[0008] In recent years, the integration of electrical components has led to the miniaturization of each electrical component. Miniaturized electrical components have a smaller heat dissipation area, so they require high heat resistance. When the insulating layer covering the soft magnetic iron powder deteriorates due to heat, the eddy current loss reduction performance decreases, and the iron loss of the dust core exposed to high temperature environments increases.

[0009] The present invention has been proposed to solve the above-mentioned problems, and an object of the present invention is to provide a powder for dust cores in which iron loss is unlikely to increase even when exposed to a high-temperature environment, a manufacturing method thereof, a dust core using this powder for dust cores, and a manufacturing method thereof. [Means for solving the problem]

[0010] In order to achieve the above object, the powder for dust core according to the embodiment comprises a soft magnetic iron powder and a mixed layer of diphenyldimethoxysilane and a silicone resin that coats a part or all of the soft magnetic iron powder.

[0011] The diphenyldimethoxysilane may be contained in the mixed layer at a ratio of 0.20 wt % to 1.5 wt % relative to the soft magnetic iron powder.

[0012] The mixed layer may have a cross-linked structure in which the diphenyldimethoxysilane cross-links the silicone resin.

[0013] A dust core containing these powders for dust cores is also one aspect of the present invention.

[0014] In order to achieve the above object, the method for producing a powder for dust cores according to an embodiment of the present invention includes a mixing step of simultaneously mixing diphenyldimethoxysilane and a silicone resin with a soft magnetic iron powder, and a drying step of drying the resulting mixture at a temperature lower than the boiling point of the diphenyldimethoxysilane after the mixing step.

[0015] Furthermore, in order to achieve the above object, a manufacturing method for a dust core according to an embodiment of the present invention includes a mixing step of simultaneously mixing diphenyldimethoxysilane and a silicone resin with a soft magnetic iron powder, a drying step of drying the mixture at a temperature lower than the boiling point of the diphenyldimethoxysilane after the mixing step, a pressure molding step of pressure molding the powder after the drying step, and an annealing step of annealing the molded body after the pressure molding step and causing a crosslinking reaction of the diphenyldimethoxysilane. Effect of the Invention

[0016] According to the present invention, an increase in core loss of a powder magnetic core can be suppressed even in a high-temperature environment. [Brief description of the drawings]

[0017] [Figure 1] 4 is a bar graph showing iron loss deterioration rates of Example 1 and Comparative Examples 1 and 2. [Diagram 2] 1 is a bar graph showing the iron loss deterioration rates of Example 2 and Comparative Examples 3 and 2. [Diagram 3] FIG. 1 is a scatter diagram showing the relationship between the amount of diphenyldimethoxysilane added and the iron loss deterioration rate. [Figure 4] FIG. 1 is a scatter diagram showing iron loss for each amount of diphenyldimethoxysilane added. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The powder for dust core and the dust core according to the present embodiment will be described in detail below. Note that the present invention is not limited to the embodiment described below.

[0019] (Schematic configuration) A powder core is a magnetic material used in the core of a coil, also called an inductor or reactor. A powder core is formed by compressing powder for a powder core. This powder for a powder core has a core of soft magnetic iron powder. The soft magnetic iron powder is covered with a mixed layer of diphenyldimethoxysilane and silicone resin. The mixed layer is an insulating layer that insulates the soft magnetic iron powder, and is formed by an insulation treatment process. A powder core is produced through a molding process in which the powder for a powder core is pressure-molded into a desired shape to form a molded body, and an annealing process in which the molded body is annealed.

[0020] (Soft magnetic iron powder) Soft magnetic iron powders are mainly composed of iron. Examples of soft magnetic iron powders include pure iron powder, permalloys (Fe-Ni alloys) mainly composed of iron, Si-containing iron alloys (Fe-Si alloys), sendust alloys (Fe-Si-Al alloys), and mixtures of two or more of these powders.

[0021] The pure iron powder contains 99% or more Fe. The Si-containing iron alloy may contain Co, Al, Cr, or Mn. When using permalloy (Fe-Ni alloy), the ratio of Fe to Ni is preferably 50:50 or 25:75, but other ratios are also acceptable. For example, Fe-80Ni or Fe-36Ni may be used. In addition to Fe and Ni, Si, Cr, Mo, Cu, Nb, Ta, etc. may be contained.

[0022] Examples of Fe-Si alloy powder include Fe-3.5%Si alloy powder and Fe-6.5%Si alloy powder, but the ratio of Si to Fe may be other than 3.5% or 6.5%. Fe-Si-Al alloy is a ternary alloy made of iron, silicon and aluminum, and contains, for example, about 6wt% to 10wt% Si and about 4wt% to 5wt% Al relative to Fe, but may also contain about 1wt% to 3wt% Ni relative to Fe, and may further contain Co, Cr or Mn.

[0023] This soft magnetic iron powder may be produced by a pulverization method or an atomization method. The atomization method may be any of water atomization, gas atomization, and water gas atomization. Currently, water atomization is the most readily available and low cost method. When water atomization is used, the particle shape is irregular, so that it is easy to improve the mechanical strength of the powder molded body obtained by pressure molding the particles, which is preferable. The gas atomization method is preferable because it can effectively reduce hysteresis loss.

[0024] The soft magnetic iron powder preferably has a small specific surface area. In other words, it is preferable that the sphericity is high. If the specific surface area is small, the gaps between the soft magnetic iron powder particles are small, and the density and magnetic permeability can be improved. The average circularity of the particles can be increased by smoothing the surface irregularities using a ball mill, mechanical alloying, jet mill, attritor, or surface modification device.

[0025] The soft magnetic iron powder is preferably heat-treated in a non-oxidizing atmosphere. The non-oxidizing atmosphere is preferably a low-oxygen atmosphere with an oxygen concentration of 0.01%, for example, an inert gas atmosphere, or a reducing gas atmosphere. Examples of the inert gas include noble gases such as Ar and N2. Examples of the reducing gas include H2. The heating time is, for example, about 1 to 6 hours. In this heat treatment step, it is preferable to expose the soft magnetic iron powder to a temperature environment of 500°C to 700°C. By exposing the soft magnetic iron powder to a temperature environment of 500°C to 700°C, the effect of reducing hysteresis loss can be obtained.

[0026] (insulating layer) The insulating layer ensures electrical insulation between the particles of the soft magnetic iron powder and reduces eddy current loss in the powder core. The insulating layer also acts as a binder, improving shape retention during molding and further increasing the strength of the molded body after annealing. It also improves the density of the soft magnetic iron powder and increases the magnetic permeability of the powder core.

[0027] The insulating layer may be attached so as to cover the entire surface of the soft magnetic iron powder, or may be attached so as to cover a portion of the surface of the powder, or both of these modes may be mixed in the powder for powder core. In addition, each particle of the insulating resin constituting the insulating layer may be attached to the surface of the soft magnetic iron powder, or an aggregate of the insulating resin constituting the insulating layer may be attached to the surface of the soft magnetic iron powder, or both of these modes may be mixed in the powder for powder core. When the particles or aggregates of the insulating resin constituting the insulating layer cover a portion of the surface of the soft magnetic iron powder, the particles or aggregates of the insulating resin constituting the insulating layer may be dispersed in dots and attached, or may be dispersed in lumps and attached, or these modes may be mixed.

[0028] The insulating layer contains a silicone resin. Silicone resin is a resin having a siloxane bond (Si-O-Si) as the main skeleton, and has a three-dimensional network structure by, for example, thermal curing by dehydration condensation, and can form a hard insulating layer with excellent flexibility. Typical examples of silicone resins include methyl-based, methylphenyl-based, propylphenyl-based, epoxy resin-modified, alkyd resin-modified, polyester resin-modified, and rubber-based silicone resins. More preferably, when a methylphenyl-based silicone resin is used as the silicone resin, an insulating layer with little loss on heating and excellent heat resistance can be formed.

[0029] The amount of silicone resin added is preferably 0.6wt% to 2.5wt%, more preferably 0.8wt% to 2.0wt%, based on the soft magnetic iron powder. If the amount added is less than 0.6wt%, it will not function as an insulating layer, and the magnetic properties will deteriorate due to increased eddy current loss, and the silicone resin will not function as a binder, resulting in a decrease in strength. If the amount added is more than 2.5wt%, it will result in a decrease in the density of the powder magnetic core.

[0030] This insulating layer contains a silane compound in addition to the silicone resin. The insulating layer is a mixed layer in which the silicone resin and the silane compound are mixed together. To form the mixed layer, the insulating process includes a mixing process in which the soft magnetic iron powder, the silicone resin, and the silane compound are mixed simultaneously. The drying process in the insulating process is started after the soft magnetic iron powder, the silicone resin, and the silane compound are mixed.

[0031] If there is no drying step between the introduction of the silicone resin into the mixer and the introduction of the silane compound into the mixer, that step is included in the simultaneous mixing. Either the silicone resin or the silane compound may be mixed with the soft magnetic iron powder, and the other may be introduced and mixed, and then the drying step may be carried out, or the silicone resin and the silane compound may be introduced into the mixer, and then mixed, and then the drying step may be carried out.

[0032] Here, diphenyldimethoxysilane is used as the silane compound. That is, the mixed layer is a layer in which silicone resin and diphenyldimethoxysilane are mixed. Diphenyldimethoxysilane is a high-boiling point silane compound with a high boiling point of 304°C. In the drying process of the insulation treatment process, the mixture can be dried in a temperature environment below the boiling point of diphenyldimethoxysilane, and the volatilization of diphenyldimethoxysilane can be suppressed.

[0033] If diphenyldimethoxysilane does not volatilize during the drying process in the insulation process, the crosslinking reaction of diphenyldimethoxysilane can be promoted in the annealing process in which the molded body of the powder magnetic core is annealed. Therefore, a crosslinking structure in which the silicone resin is crosslinked with diphenyldimethoxysilane is added to the three-dimensional network structure of the silicone resin. The addition of this crosslinking structure reinforces the insulating layer and adds high heat resistance to the insulating layer. In order to realize this crosslinking structure, the silane compound is phenyldimethoxysilane, which has a methoxy group and a phenyl group of the silicone resin and has a high boiling point.

[0034] When the silane compound layer and the silicone resin layer are separated, the silane compound layer modifies the wettability of the soft magnetic iron powder, and improves the bonding between the soft magnetic iron powder and the silicone resin layer. However, the silicone resin layer cannot be reinforced, and the heat resistance of the silicone resin layer cannot be improved. Therefore, the silane compound is diphenyldimethoxysilane, which is simultaneously mixed with the silicone resin to form a mixed layer of diphenyldimethoxysilane and silicone resin, and the diphenyldimethoxysilane functions as a crosslinking agent in the annealing process.

[0035] Furthermore, if the cross-linking reaction of the silane compound is accelerated during the drying step in the insulation treatment process, the flexibility of the insulating layer may decrease, and the insulating layer may be damaged during the pressure molding step for manufacturing the powder magnetic core, which may increase the eddy current loss of the powder magnetic core. Therefore, in order to suppress the cross-linking reaction during the drying step, diphenyldimethoxysilane is used as the silane compound.

[0036] The amount of diphenyldimethoxysilane added is preferably 0.20 wt% or more relative to the soft magnetic iron powder. When it is 0.20 wt% or more, the heat resistance of the insulating layer is further improved, it does not deteriorate due to high heat, and the increase in iron loss of the powder magnetic core is further suppressed even in a high-temperature environment. Moreover, the amount of diphenyldimethoxysilane added is preferably 1.5 wt% or less relative to the soft magnetic iron powder. When it is 1.5 wt% or less, the iron loss itself is kept low, and the increase in iron loss of the powder magnetic core is suppressed in a high-temperature environment.

[0037] Thus, the mixed layer of silicone resin and diphenyldimethoxysilane has excellent heat resistance and prevents the deterioration of insulation performance even in a high-temperature environment. Therefore, the increase in iron loss of the powder core can be suppressed even in a high-temperature environment. The drying temperature is preferably 120°C or higher and 250°C or lower. The drying time is, for example, about 2 hours.

[0038] (powder magnetic core) Powder cores are produced through a molding process in which powder for powder cores is pressure-molded into a desired shape to form a molded body, and an annealing process in which the molded body is annealed. The pressure during molding is 7 to 20 ton / cm. 2 The average is 12 to 15 ton / cm 2 It is preferable that the powder for powdered magnetic core is subjected to a lubricant adding process prior to the molding process, which reduces the pressure required to release the upper punch during molding, prevents the powder for powdered magnetic core from sticking to the die, and improves the quality of the molded body. In addition, it is preferable to pass the soft magnetic iron powder through a sieve with a specified mesh size prior to the molding process in order to eliminate aggregation of the soft magnetic iron powder.

[0039] The lubricant coats the surface of the insulating layer coated with the soft magnetic iron powder. Examples of the lubricant include, but are not limited to, stearic acid and its metal salts, as well as ethylene bisstearamide, ethylene bisstearamide, and ethylene bisstearamide. The amount of the lubricant added is preferably about 0.2 wt% to 0.8 wt% relative to the soft magnetic iron powder. More preferably, the amount of the lubricant added is about 0.3 wt% to 0.6 wt% relative to the soft magnetic iron powder. By setting the amount within this range, the slip between the soft magnetic iron powder particles can be further improved. The lubricant may be used when adding and mixing a silane compound, a silicone resin, or a combination of these in the insulation treatment process.

[0040] In the annealing process, the molded body that has undergone the molding process is heated to remove distortion. In addition, the crosslinking reaction between diphenyldimethoxysilane and silicone resin is promoted, and a crosslinked structure of silicone resin by diphenyldimethoxysilane is formed. The heating environment is a non-oxidizing atmosphere such as nitrogen gas, a mixed gas of nitrogen and hydrogen, or a low-oxygen atmosphere such as 0.01%, or the air, and the temperature is 600°C or higher and lower than the temperature at which the insulating layer coated on the powder for dust core is destroyed (for example, 800°C).

[0041] In such powders for dust cores and dust cores, the mixed layer in which diphenyldimethoxysilane and silicone resin are mixed has high heat resistance and is less likely to deteriorate in high-temperature environments, thereby suppressing the increase in iron loss due to exposure to high heat. EXAMPLES

[0042] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0043] The powder for the dust core of Example 1 was prepared as follows, and the dust core was prepared using the powder for the dust core. Fe-Si alloy powder was used as the soft magnetic iron powder. In the insulation treatment process, 0.5 wt% of diphenyldimethoxysilane and 1.2 wt% of silicone resin were added to and mixed with the Fe-Si alloy powder, and the mixture was dried for 2 hours in a temperature environment of 200°C. The diphenyldimethoxysilane used was model number KBM-202SS manufactured by Shin-Etsu Chemical Co., Ltd., which has a molecular weight of 244.4, a specific gravity of 1.08, and a boiling point of 304°C.

[0044] After the insulation treatment, the powder for the dust core was sieved to eliminate agglomerations. Then, 0.45 wt% zinc stearate was added and mixed as a lubricant to the powder for the dust core. The powder for the dust core with the lubricant added was filled into a mold and press molded to obtain a toroidal molded body with an outer diameter of 16.5 mm, an inner diameter of 11.0 mm, and a height of 5.0 mm. The pressure for the press molding was 9.5 ton / cm. 2 After the molded body was produced, this molded body was placed in a reducing atmosphere containing 5% hydrogen, and sintered at 640° C. for 2 hours. In this way, the dust core of Example 1 was produced.

[0045] A dust core was also produced in Comparative Example 1. In the dust core in Comparative Example 1, the insulating layer of diphenyldimethoxysilane and the insulating layer of silicone resin were separate layers. First, 0.5 wt% of diphenyldimethoxysilane was added to and mixed with the Fe-Si alloy powder, and the mixture was dried in a temperature environment of 150°C for 2 hours.

[0046] After forming an insulating layer of diphenyldimethoxysilane on the surface of the soft magnetic iron powder, the outer shell was further covered with an insulating layer of silicone resin. That is, after drying of the insulating layer of diphenyldimethoxysilane was completed, 1.2 wt% of silicone resin was added and mixed with the soft magnetic iron powder having the insulating layer of diphenyldimethoxysilane, and dried in a temperature environment of 200°C for 2 hours.

[0047] Except for the fact that diphenyldimethoxysilane and silicone resin were mixed separately and the insulating layer was formed as a separate layer, the manufacturing method, manufacturing conditions, and composition of the powder for the powder core in Comparative Example 1, and the manufacturing method, manufacturing conditions, and composition of the powder core in Comparative Example 1 were the same as those in Example 1.

[0048] A powder magnetic core was also produced according to Comparative Example 2. The insulating layer of the powder for powder magnetic cores according to Comparative Example 2 contained a silicone resin but did not contain a silane compound. Except for the absence of a silane compound, the manufacturing method, manufacturing conditions, and composition of the powder for powder magnetic cores according to Comparative Example 2, and the manufacturing method, manufacturing conditions, and composition of the powder magnetic core according to Comparative Example 2 were the same as those of Example 1.

[0049] The powder magnetic cores of Example 1, Comparative Example 1, and Comparative Example 2 were exposed to a temperature environment of 250° C. The iron loss (Pcv) of the powder magnetic cores was measured before and after this high-temperature test, and the Pcv deterioration rate was calculated. The initial iron loss before the high-temperature test and the iron loss after exposure to a temperature environment of 250° C. for 100 hours were measured.

[0050] When measuring the iron loss, 17 turns of φ0.5 mm copper wire were wound around the powder magnetic core as the primary winding and 17 turns as the secondary winding. Then, using a BH analyzer (Iwatsu Measurement Corporation: SY-8219), which is a magnetic measuring device, the iron loss Pcv (kW / m 3 The Pcv degradation rate was calculated by subtracting the iron loss before the high-temperature test from the iron loss after the high-temperature test, dividing the difference by the initial iron loss before the high-temperature test, and converting it into a percentage.

[0051] Table 1 below shows the initial iron loss, the iron loss after 100 hours of exposure to a temperature environment of 250°C, and the Pcv degradation rate for Example 1, Comparative Example 1, and Comparative Example 2. In the table, the initial iron loss is shown in the Pcv:0hr column, and the iron loss after 100 hours of exposure to a high temperature environment of 250°C is shown in the Pcv:100hr column. (Table 1) TIFF0007603644000001.tif63163

[0052] FIG. 1 is a bar graph showing the iron loss deterioration rate of Example 1, Comparative Example 1, and Comparative Example 2 based on Table 1 above. As can be seen from Table 1 and Comparative Example 1 and Comparative Example 2 in FIG. 1, when an insulating layer of a silane compound is interposed between the insulating layer of the silicone resin and the soft magnetic iron powder, the Pcv deterioration rate can be kept low even when the powder core is exposed to a high temperature environment of 250 ° C. This is because the layer of the silane compound improves the wettability of the soft magnetic iron powder, and the layer of the silane compound improves the binding between the soft magnetic iron powder and the layer of the silicone resin. However, the powder core of Comparative Example 1 has a high absolute value of iron loss, and when exposed to a high temperature environment of 250 ° C., the absolute value of iron loss becomes equivalent to that of Comparative Example 2.

[0053] On the other hand, as shown by Example 1 and Comparative Example 1 in Table 1 and FIG. 1, the Pcv degradation rate of Example 1 is suppressed to be lower than that of Comparative Example 1 even when exposed to a high-temperature environment of 250°C. Moreover, since the iron loss of Example 1 has a low absolute value and a low Pcv degradation rate, when exposed to a high-temperature environment of 250°C, the difference with Comparative Example 1 is enlarged and good performance is maintained. In this way, it was confirmed that coating the soft magnetic iron powder with a mixed layer of a silane compound and a silicone resin improves the heat resistance of the insulating layer and suppresses the iron loss of the powder magnetic core to be low even in a high-temperature environment.

[0054] Furthermore, dust cores of Example 2 and Comparative Example 3 were produced. In the dust core of Comparative Example 3, the silane compound mixed into the mixed layer together with the silicone resin is methyltrimethoxysilane, which is different from that in Example 1. For the methyltrimethoxysilane, model number TES28 manufactured by Wacker Asahi Kasei Silicone Co., Ltd., which has a molecular weight of 136.2, a specific gravity of 0.95, and a boiling point of 102°C, is used, and its boiling point is lower than the drying temperature of 200°C during the manufacturing process of the powder for dust cores.

[0055] In Example 2 and Comparative Example 3, the silane compound was mixed with the Fe-Si alloy powder at a ratio of 0.35 wt %. The manufacturing method, manufacturing conditions, and composition of the powder for the powder core, and the manufacturing method, manufacturing conditions, and composition of the powder core, in Example 2 and Comparative Example 3, were otherwise the same as in Example 1.

[0056] The powder magnetic cores of Example 2, Comparative Example 2, and Comparative Example 3 were exposed to a temperature environment of 250°C. The iron loss (Pcv) of the powder magnetic cores was measured before and after this high-temperature test, and the Pcv degradation rate was calculated. The initial iron loss before the high-temperature test and the iron loss after exposure to a temperature environment of 250°C for 100 hours were measured. The method of measuring the iron loss and the method of calculating the Pcv degradation rate were the same as in Example 1.

[0057] Table 2 below shows the initial iron loss, the iron loss after 100 hours of exposure to a temperature environment of 250°C, and the Pcv degradation rate for Example 2, Comparative Example 2, and Comparative Example 3. In the table, the initial iron loss is shown in the Pcv:0hr column, and the iron loss after 100 hours of exposure to a high temperature environment of 250°C is shown in the Pcv:100hr column. (Table 2) TIFF0007603644000002.tif62163

[0058] Fig. 2 is a bar graph showing the iron loss degradation rates of Example 2, Comparative Example 3, and Comparative Example 2 based on Table 2 above. As can be seen from Table 2 and Comparative Examples 2 and 3 in Fig. 2, when soft magnetic iron powder is coated with a mixed layer of a silane compound and a silicone resin, it has been confirmed that unless the silane compound is diphenyldimethoxysilane, the heat resistance of the insulating layer is significantly reduced and the iron loss of the powder magnetic core increases significantly even in a high temperature environment.

[0059] On the other hand, as can be seen from Example 2 and Comparative Example 3 in Table 2 and Figure 2, when the silane compound is diphenyldimethoxysilane, the heat resistance of the insulating layer is improved and the increase in iron loss of the powder core is suppressed even in a high-temperature environment. In general, it was confirmed that when the silane compound is diphenyldimethoxysilane and the soft magnetic iron powder is coated with a mixed layer of diphenyldimethoxysilane and silicone resin, the heat resistance of the insulating layer is improved and the increase in iron loss of the powder core is suppressed even in a high-temperature environment.

[0060] Next, the amount of diphenyldimethoxysilane added was changed as shown in Table 3 below, and the initial iron loss for each amount added and the iron loss after 100 hours of exposure to a temperature environment of 250°C were measured, and the Pcv degradation rate was calculated. The amount of silane compound added is the weight ratio to the soft magnetic iron powder. The amount of silicone resin added is the weight ratio to the soft magnetic iron powder.

[0061] (Table 3) TIFF0007603644000003.tif152159

[0062] FIG. 3 is a scatter diagram showing the iron loss degradation rate for each amount of diphenyldimethoxysilane added based on Table 3 above. FIG. 4 is a scatter diagram showing the iron loss (Pcv: 0hr in the figure) for each amount of diphenyldimethoxysilane added based on Table 3 above. As shown in Table 3 and FIG. 3, when the amount of diphenyldimethoxysilane added is 0.20wt% or more, the Pcv degradation rate is particularly low, the heat resistance of the insulating layer is improved, and it was confirmed that the increase in iron loss of the powder magnetic core is suppressed even in a high temperature environment. Also, as shown in Table 3 and FIG. 4, it was confirmed that when the amount of diphenyldimethoxysilane added is 1.5wt% or less, the iron loss itself is suppressed particularly low.

[0063] (Other embodiments) The above-mentioned embodiments and examples of the present invention are presented as examples, and the present invention is not limited to the above-mentioned embodiments and examples. The above-mentioned embodiments and examples can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the scope of the invention. The embodiments, examples, and their modifications are included in the scope of the present invention.

Claims

1. Soft magnetic iron powder; a mixed layer of diphenyldimethoxysilane and silicone resin, which coats a part or all of the soft magnetic iron powder; To have A powder for dust cores characterized by:

2. The diphenyldimethoxysilane is contained in the mixed layer at a ratio of 0.20 wt % to 1.5 wt % with respect to the soft magnetic iron powder; The powder for dust cores according to claim 1 ,

3. the mixed layer has a crosslinked structure in which the diphenyldimethoxysilane crosslinks the silicone resin; The powder for dust cores according to claim 1 ,

4. The powder for dust core according to any one of claims 1 to 3 is contained. A powder magnetic core characterized by:

5. A mixing step of simultaneously mixing diphenyldimethoxysilane and a silicone resin with a soft magnetic iron powder; a drying step of drying the mixture at a temperature lower than the boiling point of the diphenyldimethoxysilane after the mixing step; containing, A method for producing powder for dust cores, comprising the steps of:

6. A mixing step of simultaneously mixing diphenyldimethoxysilane and a silicone resin with a soft magnetic iron powder; a drying step of drying the mixture at a temperature lower than the boiling point of the diphenyldimethoxysilane after the mixing step; a pressure molding step of pressure molding the powder after the drying step; an annealing step of annealing the molded body after the pressure molding step and crosslinking the diphenyldimethoxysilane; containing, A method for producing a powder magnetic core, comprising the steps of:

Citation Information

Patent Citations

  • Composition for resin bonding magnet and manufacture thereof

    JP1999126710A

  • Dust core

    JP2002083709A

  • Iron base powder and dust core using the same, and method of manufacturing iron base powder

    JP2003303711A

  • Dust core and method of manufacturing the same

    JP2010219161A

  • Condensation curable organopolysiloxane composition, condensation curable organopolysiloxane composition kit and silicone rubber

    JP2017057386A